Pengaruh Return On Equity dan Debt To Equity Ratio terhadap Return Saham dengan Price To Book Value sebagai Variabel Intervening - Sonya Dwi Monita (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the effect of Return On Equity (ROE) and Debt Equity Ratio (DER) on stock returns with Price To Book Value (PBV) as an intervening variable in Manufacturing companies listed on the Indonesia Stock Exchange 2017-2021. The sample in this study was taken by purposive sampling method on manufacturing stocks listed on the Indonesia Stock Exchange 2017-2021. The number of samples used as many as 118 companies. The analytical method of this research is using multiple linear regression analysis method. The results of this study indicate that Return On Equity (ROE) has a significant effect on Price To Book Value (PBV), Debt Equity Ratio (DER) has a significant effect on Price To Book Value (PBV), Return On Equity (ROE) has a significant effect on Return Stocks, Debt Equity Ratio (DER) is not significant on Stock Returns, Price To Book Value (PBV) has a significant effect on Stock Returns, Return On Equity (ROE) does not mediate on stock returns through Price To Book Value (PBV) as an intervening variable, Debt Equity Ratio (DER) does not mediate stock returns through Price To Book Value (PBV) as an intervening variable in Manufacturing companies listed on the Indonesia Stock Exchange 2017-2021